PENGEMBANGAN MEDIA AUDIO VISUAL INTERAKTIF BERBASIS ANIMASI DALAM PEMBELAJARAN IPA TENTANG TUMBUHAN DAN FUNGSINYA - Ain, Nafilatul; Fashokha, Ning; Rohmah, Muflihatur; Sulthoniyah, Luluk (Universitas Tanjungpura, 2023)
The purpose of this research is to analyze more deeply how the development of audio-visual animation learning media in science learning and its effectiveness in learning. This research uses the method of literature review or Library Research. Data collection through previous journals, then analyzed and developed again. The results of this study are the discovery of various problems in learning science from both internal and external factors. Internal factors in science learning include the teacher's unpreparedness in using learning media, the teacher has not mastered the use of learning media and the low interest in learning of students. External factors include curriculum, programs, facilities and infrastructure that do not support. The use of audio-visual learning media is applied by teachers in science learning about plants and their functions are very effective in learning activities, students participate in learning activities enthusiastically and listen well. This animated audio-visual learning media is very interesting, so it can attract students' attention and they can understand the subject matter more easily and make learning activities fun.